Multicultural Islamic Education In Fostering Tolerance: Strategies And Challenges In Indonesia - Sutrisno; Solikah, Imroatus; Wardini, Sevia Umi (CV. Gerasi Insan Nusantara, 2025)
Indonesia as a country with cultural, ethnic, and religious diversity presents challenges in building tolerance between religious communities. Islamic education has an important role in fostering a tolerant attitude through a multicultural approach, which integrates the value of respect for differences in the learning process. This study aims to explore the strategy of multicultural Islamic education in fostering tolerance, identify the challenges faced, and provide strategic recommendations for the development of a more inclusive Islamic education curriculum and policy. The research method uses a qualitative approach with a literature review, which involves the study of literature from books, journals, articles, and academic sources related to multicultural Islamic education and tolerance. Data were analyzed descriptively qualitatively to identify strategies and challenges in their implementation. The results of the study show that effective strategies include the integration of multicultural values ​​in the curriculum, teacher training to improve competence in teaching tolerance, and the use of dialogical methods that involve students and the community. Significant challenges include cultural resistance, limited educational resources, and negative perceptions of pluralism. The implications of this study are the importance of improving teacher training, developing an inclusive curriculum, and increasing public awareness of pluralism. This study provides a basis for policy makers in designing more responsive education programs, supporting the creation of a harmonious and tolerant Indonesian society.